2022
DOI: 10.3389/fphar.2022.808848
|View full text |Cite
|
Sign up to set email alerts
|

Potentially Hazardous Drug-Drug Interactions Associated With Oral Antineoplastic Agents Prescribed in Chinese Tertiary Care Teaching Hospital Settings: A Multicenter Cross-Sectional Study

Abstract: Background: Oral administration increases the risk of interactions, because most oral antineoplastic agents (OAAs) are taken on a daily basis. Interactions can increase exposure to antitumoral agents or cause treatment failure. Potential drug–drug interactions (DDIs) are commonly observed in patients with cancer, while the extent to which OAAs related hazardous DDIs remains unclear.Methods: We studied the contraindication patterns between oral antineoplastic agents and other medications among cancer patients i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
1
1
0
Order By: Relevance
“…A study of potential DDI with imatinib, performed in 544 French patients with at least one prescription of imatinib, a substrate and inhibitor of CYP3A4, revealed that dexamethasone, which was prescribed in as much as 23% of patients, was the third potentially interacting agent involved (after Paracetamol and proton pump inhibitors), leading to specific recommendations to prescribers [12]. This is consistent with a Chinese study on potential DDI with every oral antineoplastic agent (13.917 patients), which found interaction between these oral chemotherapies and dexamethasone in 117 patients (39% of every registered DDI in this study) [13]. Nevertheless, the real impact of such DDI with dexamethasone remains poorly defined, as shown in a recent review of six databases of DDI between COVID-19 treatments and, respectively, cardiovascular and antidiabetic agents, where dexamethasone was described as a "moderate risk of DDI which requires caution and close monitoring" with all 19 anti-diabetic, anti-hypertensive and cardiovascular system-acting agents screened in this study [14].…”
Section: Dexamethasone An Increasingly Used Moleculesupporting
confidence: 89%
“…A study of potential DDI with imatinib, performed in 544 French patients with at least one prescription of imatinib, a substrate and inhibitor of CYP3A4, revealed that dexamethasone, which was prescribed in as much as 23% of patients, was the third potentially interacting agent involved (after Paracetamol and proton pump inhibitors), leading to specific recommendations to prescribers [12]. This is consistent with a Chinese study on potential DDI with every oral antineoplastic agent (13.917 patients), which found interaction between these oral chemotherapies and dexamethasone in 117 patients (39% of every registered DDI in this study) [13]. Nevertheless, the real impact of such DDI with dexamethasone remains poorly defined, as shown in a recent review of six databases of DDI between COVID-19 treatments and, respectively, cardiovascular and antidiabetic agents, where dexamethasone was described as a "moderate risk of DDI which requires caution and close monitoring" with all 19 anti-diabetic, anti-hypertensive and cardiovascular system-acting agents screened in this study [14].…”
Section: Dexamethasone An Increasingly Used Moleculesupporting
confidence: 89%
“…2) Although, according to previous study report, over 40% of patients experienced adverse effects caused by DDI with oral cancer therapies such as TKIs, clinical practice only relying on person experience with scarcity of guidance. 6) Still, FDA provides guidance for DDIs in clinical aspects during drug development, which did not provide detailed explanations of DDIs between investigational drugs and concomitant medication based on specific drugs. 7) However, only the guideline indicates sponsors should assess the DDI potential before investigational drug administered with concomitant medications such as antifungal agents to patients.…”
mentioning
confidence: 99%